Effect of Ficus hispida L. on normal and dexamethasone suppressed wound healing (Brazilian Journal of Pharmaceutical Sciences, 2011)
Ethanolic extract of roots of Ficus hispida was investigated in normal and dexamethasone depressed healing conditions, using incision, excision and dead space wound models in albino rats. The root extract of Ficus hispida has shown the maximum breaking strength compared to control group. The rate of epithelialization and wound contraction in excision model was better as compared to control groups. There was significant increase in granulation tissue weight and hydroxyproline content in dead space model compared to control group. The antihealing effect of dexamethasone was also reverted by the administration of ethanolic extract of Ficus hispida in all the wound models .The results indicated that the root extract of Ficus hispida has a significant wound healing activity and also promotes healing in dexamethasone depressed healing conditions.